Laboratory Investigation of Cryptosporidiosis and Giardiasis in Children With Diarrhoea; A Hospital Based Study - Rathnayake, R.G.L.; Ranchigoda, C.M.; Roshan, R.G.; Samarasinghe, S.; Banneheke, B.M.H.A. (Proceedings of 8th International Research Conference, KDU, Published November 2015, 2015)
Attached
Keywords: Cryptosporidium; Giardia; diarrheoa